STAT5 and STAT5 Inhibitors in Hematological Malignancies - Tolomeo, Manlio; Meli, Maria; Grimaudo, Stefania (Anti-Cancer Agents in Medicinal Chemistry, 2019)
The JAK-STAT pathway is an important physiologic regulator of different cellular functions including proliferation, apoptosis, differentiation, and immunological responses. Out of six different STAT proteins, STAT5 plays its main role in hematopoiesis and constitutive STAT5 activation seems to be a key event in the pathogenesis of several hematological malignancies. This has led many researchers to develop compounds capable of inhibiting STAT5 activation or interfering with its functions. Several anti-STAT5 molecules have shown potent STAT5 inhibitory activity in vitro. However, compared to the large amount of clinical studies with JAK inhibitors that are currently widely used in the clinics to treat myeloproliferative disorders, the clinical trials with STAT5 inhibitors are very limited. At present, a few STAT5 inhibitors are in phase I or II clinical trials for the treatment of leukemias and graft vs host disease. These studies seem to indicate that such compounds could be well tolerated and useful in reducing the occurrence of resistance to tyrosine kinase inhibitors in chronic myeloid leukemia. Of interest, STAT5 seems to play an important role in the regulation of hematopoietic stem cell self-renewal suggesting that combination therapies including STAT5 inhibitors can erode the cancer stem cell pool and possibly open the way for the complete cancer eradication. In this review, we discuss the implication of STAT5 in hematological malignancies and the results obtained with the novel STAT5 inhibitors.
Keywords: STAT transcription factors